Enteric Opportunistic Infection and the Impact of Antiretroviral Therapy among HIV/AIDS Patients from Tehran, Iran - Hossein MASOUMI-ASL; Khadijeh KHANALIHA; Farah BOKHARAEI-SALIM; Abdoulreza ESTEGHAMATI; Saeed KALANTARI; Maryam HOSSEINYRAD (Tehran University of Medical Sciences, 2019)
Background: Opportunistic parasites have been identified as human pathogens, especially in immunodeficient patients. Microsporidian and coccidian infections cause chronic diarrhea as common clinical manifestation in HIV positive patients. In this study, the frequency of opportunistic infections, including microsporidian and coccidian infections, was evaluated in HIV/AIDS patients from Tehran and phylogenic analysis was performed for E. bieneusi isolates from these patients.  Methods: One hundred and two stool samples were collected from confirmed HIV/AIDS patients, referred to Consult Center of Behavior Diseases, West Health Center, Iran University of Medical Sciences in Tehran, Iran. The samples were transferred to Research Center of Pediatric Infectious Diseases, Institute of Immunology and Infectious Diseases, Iran University of Medical Sciences from Jan 2016 to Dec 2016. After conventional formalin-ether concentration, aniline blue staining method and acid-fast staining technique were used for detection of microsporidian spores and Cyclospora oocysts. DNA was extracted and nested PCR was performed. Results: Two (1.96%) cases were found to be positive for intestinal microsporidia infection using aniline blue staining method and were confirmed as E. bieneusi by nested PCR. One patient was found with Cyclospora cayetanensis infection by acid-fast staining method and PCR. Giardia lamblia and Blastocystis hominis were detected as non-opportunistic parasites in 1/102 (0.98%) and 2/102 (1.96%) of the HIV positive patients, respectively. Conclusion: With respect to the use of antiretroviral therapy (ART) in HIV positive patients, we found a low frequency of infection.